Implementation of Facility and Safety Management at Public Health Center Pesantren II Kediri - Rindang Farihah; Eltrik Setiyawan; Agus Setyono; Dede Kurniawati; Rohmatun Naja; Indasah; Siti Rahmah (Universitas STRADA Indonesia, 2024)
Health Health centers must be accredited to improve the quality of health services. In order for accreditation to be achieved, Public Health Center has requirements that must be met regarding buildings, infrastructure, equipment, and providing a safe environment for service users, visitors, officers, and the community, including patients with physical limitations. Patients with physical limitations are given access to obtain services, so facility and safety management are needed. Community service activities carried out by the Postgraduate Program in Public Health IIK Strada Indonesia, which was carried out from May 22, 2023, to June 17, 2023, aim to identify the implementation and implementation strategies for facility management and safety using Fishbone, USG, and SWOT analysis at Public Health Center Pesantren II Kediri. One of the implementations was the socialization of facility and safety management to all employees, and the results of the Wilcoxon statistical test pre-test and post-test showed a sig value. 0.000 (<0.05) means that there is an effect of socialization of facility management and security among Public Health Center Pesantran II employees. Implementation and management strategies for facilities and security management at Public Health Center Pesantren II Kediri have been well implemented. To improve service quality, there are several conditions that can be optimized. Public Health Center management has a big role to play in ensuring the management of facility management and security in accordance with applicable regulations.